45.1: Distinguished Paper: 12.2‐inch 1920 × RGBW × 720 IPS‐LCD Integrating In‐Cell Touch Panel for Automotive Use. Issue 1 (1st July 2013) - Tanaka, Chihiro; Ikeda, Kojiro; Tanaka, Toshihiko; Furutani, Naosuke; Suzuki, Daichi; Ohira, Hirofumi; Matsushima, Toshiharu; Nakamura, Akio; Tsubokura, Nobuo; Yamada, Kazuyuki; Nakamura, Keita; Shimizu, Koji; et al.
Abstract: In this paper a 12.2‐inch 1920 × RGBW × 720 prototype LCD for automotive use which integrates an in‐cell touch panel is described with some electrical and electro‐optical characteristics. In addition, the prototype of a curved‐faced and non‐rectangular form of this cited LCD is described.